Synthesis, Characterization and Electrochemical Evaluation of Layered Vanadium Phosphates as Cathode Material for Aqueous Rechargeable Zn-ion Batteries - De Luna, Yannis; Bensalah, Nasr (Frontiers in Materials, 2021)
The potential application of rechargeable multivalent ion batteries in portable devices and renewable energy grid integration have gained substantial research interest in aqueous Zn-ion batteries (ZIBs). Compared to Li-based batteries, ZIBs offer lower costs, higher energy density, and safety that make them more attractive for energy storage in grid integration applications. Currently, more research is required to find a suitable cathode material for ZIBs with high capacity and structural stability during charge/discharge cycling. Vanadium phosphate (VOP) compounds as cathode material for ZIBs have been of particular interest, owing to vanadium’s diverse oxidation states. In this present work, two VOP compounds, [H0.6(VO)3(PO4)3(H2O)3]4H2O and VOPO4.2H2O, were synthesized from phosphoric acid and different sources of vanadium via a simple and scalable hydrothermal method. Various characterization techniques were carried out, revealing the layered structure of both products and high purity of [H0.6(VO)3(PO4)3(H2O)3]4H2O. Zn/VOP batteries were prepared using Zn metal as counter and reference electrode and 3M ZnSO4.7H2O as electrolyte. Electrochemical tests were conducted to evaluate the cycling performance of VOPs as cathode material for aqueous Zn-ion batteries. Based on the results, both compounds have shown highly reversible Zn-ion intercalation and deintercalation. VOPO4.2H2O achieved a higher specific capacity of up to 85 mAh/g during discharging, as opposed to 65 mAh/g for the hydrated VOP complex. However, [H0.6(VO)3(PO4)3(H2O)3]4H2O is more stable with higher reproducibility than VOPO4.2H2O during cycling. Nevertheless, more research is still required to enhance the specific capacity and improve the cycling performance of VOP-based cathodes for their prospective use in aqueous ZIBs.